2008
DOI: 10.1002/da.20537
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and functional impairment in children with trichotillomania

Abstract: Based on an internet sample recruited from the homepage of the Trichotillomania Learning Center, data from this study suggests that symptoms of depression and anxiety may be pervasive among youth with TTM and likely impact functional impairment. Longitudinal studies using directly assessed samples are needed to replicate and extend these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…Perhaps most focal is the web-based nature of sampling. However, extant research using similar methodologies in other clinical populations have yielded robust samples and opportunities for empirically-driven hypothesis generation (Franklin et al, 2008;Lewin et al, 2009;Woods et al, 2006). Current understanding of tic severity-impairment relations is also limited by virtue of available samples.…”
Section: Limitations Of This Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Perhaps most focal is the web-based nature of sampling. However, extant research using similar methodologies in other clinical populations have yielded robust samples and opportunities for empirically-driven hypothesis generation (Franklin et al, 2008;Lewin et al, 2009;Woods et al, 2006). Current understanding of tic severity-impairment relations is also limited by virtue of available samples.…”
Section: Limitations Of This Studymentioning
confidence: 95%
“…The survey was implemented through a specialized website (surveymonkey.com) with secure and user-friendly data-gathering capability (Franklin et al, 2008;Lewin et al, 2009;Woods et al, 2006). The survey was posted online for 8 consecutive months (in 2008) as described by Conelea et al (2009).…”
Section: Data Collectionmentioning
confidence: 99%
“…Although it is unlikely that participants completed the survey without a confirmed diagnosis of PWS, it is possible that parents perusing the websites of PWS-specific agencies chose to participate in this web-based survey despite the fact that their child's diagnosis was not confirmed. However, numerous other studies of lowincidence disorders have utilized online methodology with promising results [28,53,54]. Second, due to the limited developmental functioning of many individuals with PWS [3], all measures were completed via parent-report, and the lack of direct information from children was not able to be collected.…”
Section: Limitationsmentioning
confidence: 99%
“…Using an ABAC design (Barlow, Nock, & Hersen, 2008), in which each treatment was introduced between baseline reversals, the behavior was reduced to near-zero levels and maintained at 2-month follow-up. It should be noted that the two of the previously mentioned studies used 3-year-old children with TTM as participants (Altman et al, 1982;Massong et al, 1980), and some have suggested that very young children with hair pulling might represent a distinct group from those who begin hair pulling later in childhood, such that they have a more time-limited course and favorable prognosis (Lewin et al, 2009;Santhanam, Fairley, & Rogers, 2008;Swedo et al, 1992;Tay, Levy, & Metry, 2004). This caveat may limit the generalizability of results from those two studies.…”
Section: Evidence-based Treatments For Pediatric Bfrbdsmentioning
confidence: 99%